2021
DOI: 10.1108/ejim-04-2021-0194
|View full text |Cite
|
Sign up to set email alerts
|

Identifying high quality ideas in the online context: evidence from a meta-analysis

Abstract: PurposeWith the rapid development of web-based ideation platforms, firms are increasingly reaching outside their boundaries to obtain ideas, which makes idea evaluation tricky and ineffective. Numerous studies have investigated the antecedents of idea quality, but few have focused on the fragmented and contradictory conclusions these studies have drawn. Thus, the purpose of this paper is to disentangle conflicting findings regarding factors affecting idea quality.Design/methodology/approachA total of 41 indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Comment diversity : Comment diversity here represents the diversity of content in comments to ideas, measured based on Sharon entropy (Hu and Xu, 2021), something, which indicates the diversity and uncertainty degree (Jost, 2006; Masisi et al , 2008) and potentially influences the idea acceptance (Bayus, 2013). To capture the Sharon entropy of comments, the ‘topicmodels’ package in R based on word frequency is used (Hornik and Grün, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Comment diversity : Comment diversity here represents the diversity of content in comments to ideas, measured based on Sharon entropy (Hu and Xu, 2021), something, which indicates the diversity and uncertainty degree (Jost, 2006; Masisi et al , 2008) and potentially influences the idea acceptance (Bayus, 2013). To capture the Sharon entropy of comments, the ‘topicmodels’ package in R based on word frequency is used (Hornik and Grün, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Quality ideas in OBCs are those that are not developed by the organization but have sufficient value to be implemented (Bayus, 2013), and idea quality is considered a comprehensive indicator reflecting innovation requirements from different perspectives, or the potential business value that an organization might adopt (Hu and Xu, 2021). While previous research has emphasized the importance of evaluating idea quality from multiple dimensions (Dean et al, 2006), some scholars have suggested that market potential and idea adoption are the key indicators of idea quality (Li et al, 2016;Zhu et al, 2019).…”
Section: Theoretical Background 21 Idea Quality In Obcsmentioning
confidence: 99%